Ras Guanine Nucleotide-Releasing Protein-4 Inhibits Erythropoietin Production in Diabetic Mice with Kidney Disease by Degrading HIF2A - Junmei Wang; Shuai Huang; Li Zhang; Yixian He; Xian Shao; A-Shan-Jiang A-Ni-Wan; Yan Kong; Xuying Meng; Pei Yu; Saijun Zhou (Diabetes & Metabolism Journal)
Background In acute and chronic renal inflammatory diseases, the activation of inflammatory cells is involved in the defect of erythropoietin (EPO) production. Ras guanine nucleotide-releasing protein-4 (RasGRP4) promotes renal inflammatory injury in type 2 diabetes mellitus (T2DM). Our study aimed to investigate the role and mechanism of RasGRP4 in the production of renal EPO in diabetes. Methods The degree of tissue injury was observed by pathological staining. Inflammatory cell infiltration was analyzed by immunohistochemical staining. Serum EPO levels were detected by enzyme-linked immunosorbent assay, and EPO production and renal interstitial fibrosis were analyzed by immunofluorescence. Quantitative real-time polymerase chain reaction and Western blotting were used to detect the expression of key inflammatory factors and the activation of signaling pathways. In vitro, the interaction between peripheral blood mononuclear cells (PBMCs) and C3H10T1/2 cells was investigated via cell coculture experiments. Results RasGRP4 decreased the expression of hypoxia-inducible factor 2-alpha (HIF2A) via the ubiquitination–proteasome degradation pathway and promoted myofibroblastic transformation by activating critical inflammatory pathways, consequently reducing the production of EPO in T2DM mice. Conclusion RasGRP4 participates in the production of renal EPO in diabetic mice by affecting the secretion of proinflammatory cytokines in PBMCs, degrading HIF2A, and promoting the myofibroblastic transformation of C3H10T1/2 cells.